Food and Nutrition Security - meanings and appropriations from the civil society segment of the National Council for Food and Nutrition Security - Costa, Christiane Araújo; Bógus, Cláudia Maria (Saúde e Sociedade, 2012)
In view of the huge transformations that occurred in the last two decades and of their impacts on the standards of food production and consumption, the theme of Food and Nutrition Security has been gaining momentum, approaching nourishing aspects that regard the entire population, and not just its most vulnerable segments. The importance of the civil society has been shown by the accomplishment of significant food and nutrition security experiences in its own field, as well as in partnership with the government to the formulation of proposals and actions and to their monitoring and control. As result of a research on the identification of the different meanings of the incorporation of food and nutrition security by the movements and organizations of the civil society that participate in the National Council for Food and Nutrition Security (administration 2004-2007), the appropriation of the theme could be observed in the following directions: a) privileged interaction between thematic fields from the production and consumption spheres has been favored; b) impulse to the idea of nourishing as a human right; c) ethical goal of development; d) acquisition of intra and intersector perspective; and e) necessity of an educative process of dialogic and emancipatory character.